Histopathological study of ovarian lesions at a tertiary rural hospital - Lakshmanrao Gaikwad, Sheela; Sitaram Badlani, Koshu; Dadarao Birare, Shivaji (Tropical Journal of Pathology and Microbiology, 2020)
Background:Ovaries are the third leading site of cancer among women trailing behind cervical and breast cancer according to the Indian cancer registries. The spectrum of ovarian lesions is wide with harmless simple cystic lesions at one end and the fatal aggressive malignant lesions at the other end. Thus, ovarian neoplasm offers a good field for research. The present study is aimed to observe the frequency of neoplastic and non-neoplastic lesions in a tertiary care centre of rural India. Methods: This was a prospective two years observational study and was conducted at the Department of Pathology SRTR GMC, Ambajogai, including 185 ovarian lesions. Result: Total 185 ovarian lesions were studied, 101 cases were non-neoplastic while 84 cases were neoplastic. The most common non-neoplastic lesion was corpus luteal cyst (27.7%) followed by simple ovarian cyst (24.7%) and follicular cyst (21.8%). Among 84 neoplastic cases, 74 cases (88.1%) were benign,02 cases (2.4%) were borderline tumours and 08 cases (9.5%) were diagnosed malignant. Surface epithelial tumours contributed 75% cases, while germ cell tumours and sex-cord stromal tumourcontributed 20.8% and 4.8% respectively. Conclusions: Both non-neoplastic as well as neoplastic lesions of ovary often present with similar clinical and radiological features. So histopathological study is essential to diagnose ovarian tumours and predict their prognosis.